Crescimento de seis espécies madeireiras nativas da mata atlântica sob diferentes intensidades de luz - Barros, André Junqueira (Universidade Federal de São Carlos, 2019)
The history of degradation has generated millions of hectares that demand forest restoration by landowners in the Atlantic Rain Forest and other tropical regions of the world. However, the high cost of the projects inhibits large-scale forest restoration and one way to overcome this barrier is the develop of restoration models that foresee timber production. The objective of this work was to evaluate the development of six native species of the Atlantic Rain Forest that have potential to produce timber (Anadenanthera colubrina, Balfourodendron ridelianum, Cordia trichotoma, Astronium graveolens, Cariniana legalis e Parapiptadenia rigida), planted in a forest restoration area of five years, in Araras-SP, under different intensities of light. We expected that the increase in light availability would lead to higher growth of timber species. The treatments consisted of chemical thinning (standing death) of 0, 30, 60 and 100% of the basal area of the covering trees. In 20 plots of 600 m² each, photosynthetically active radiation (PAR) and canopy opening were used to validate the chemical thinning technique and to relate them to each other and with silvicultural attributes (height, diameter and stem quality) of individuals under different intensities of light. The height, diameter at the soil level and stem quality of 1.000 individuals were sampled before and one year after treatments, to analyze growth in a shaded environment and relative growth rate after thinning, and the infestation of invasive grasses and ruderal species under different levels of light. The chemical thinning created light treatments, and the canopy opening, and PAR sampling methods showed a positive correlation. The growth of the evaluated species was slow in a shaded environment, with a positive result for C. legalis and negative for B. riedelianum. The levels of thinning affected the relative growth in trunk diameter of the species and, individually, C. legalis and C. tricochoma presented differences for relative growth rate in height and diameter, and B. riedelianum for diameter, due to the levels of thinning and PAR. The thinning provides greater light input in the understory and this may favor the growth of some species, without influencing others. Therefore, the decision to use practices to increase light levels in the understory of forest restoration plantations is species dependent.
Growth of six indiginous timber species of the atlantic rainforest under different intensities of light
Keywords: Restauração florestal; Silvicultura; Desbaste químico; Madeira; Forest restoration; Forestry; Chemical thinning; Timber; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL